Management Mechanisms and Teacher Education for Sustainable Development in Nigeria - Adaobi , Onuselogu, P; Uju., Ughamadu, F. (African Journal of Education,Science and Technology (AJEST), 2016)
A nation that is aspiring for greatness, self-sufficiency, political and economic emancipation cannot afford to escape from effective system of managing teachers’ education which can only be managed through effective management mechanisms. A teacher is an individual who must have undergone the necessary and recommended training in a teacher training institute and charged with the full responsibility of managing the classroom in such a way as to enhance the learning behavior of the learners. Therefore, this study investigated management mechanisms and teacher education for sustainable development in Nigeria. The study adopted the descriptive survey research design. The population of the study consisted of three thousand, two hundred and seventeen (3,217) personnel’s from 36 states and Abuja. The sample for the study was 370 (222 lecturers and 148 Management staff) personnels of National Teachers Institute in Nigeria, selected on the basis of six lecturers and four Management staff from each state of the 36 states and Abuja through the use of simple random sampling technique. The instrument for data collection was a 20- items questionnaire titled: Management Mechanisms and Teacher education Questionnaires (MMTEQ). Two research questions were answered using mean and standard deviation while t-test was used to test the null hypotheses at P<0.O5 level of significance. The instrument was duly validated by experts and the reliability index determined using Cronbach Coefficient Alpha which yielded 0.82 and was considered adequate for the study. Findings show that the management style does not include lecturers in decision making in managing the National Teachers Institute. Another finding also shows that lecturers generally disagreed with the style of management mechanisms used for managing the National Teachers Institute. These findings imply that there is need for effective and efficient management mechanisms in managing teachers’ education in the National Teachers Institute. It is therefore recommended that, the management staff should use regular staff meetings as a good mechanism for discussing vital issues of the National Teachers Institute administration and the management should also involve lecturers on issues about staff welfare and promotion.